Kaposi Sarcoma of the Auricle: Atypical localization - Engin Acıoğlu; Özgür Yiğit; Elad Azizli (Turkish Archives of Otorhinolaryngology, 2011)

(untitled)
Kaposi sarcoma is a well-defined, rare, low degree vascular neoplasm that shows the tendency to multifocal distribution. Especially the patients with AIDS, indicate mucosal and skin involvement. A 54 year old male patient consulted with a 0.5x0.5 cm red angiomateous lesion which developed in last 6 months on left auricle helix and a 1x1 cm red skin-swollen angiomateous which developed on crus helix. In his story, similar lesions on auricle, which are 11 and 3 years old are described. In laboratory results, there was no immunosupressive condition and the patient was HIV negative. Results of the excisional biopsy, which is made under local anesthesia to left auricle are evaluated as well-matched with Kaposi sarcoma in two different stage (nodular and patch stage). Especially in immun supressive patients with Kaposi sarcoma have the tendency to isolated auricular involvement. Therefore these patients have to be long term followed up for the lymphoma and relapse, and have to be well-examined for immun supression.